End use quality of some african corn kernels. 1. Physico-chemical characteristics of kernels and their relationshipwith the quality of lifin. a traditional whole dry-milled maize flour from Benin - Nago, Coffi Mathurnin; AKISSOE, H. NOËL; Matencio, Françoise; Mestres, Christian (My University, 1997)
The physicochemical characteristics of eight samples of lifin, a traditional maize market flour of Benin, were determined. They had very similar proximate composition and a median particle size (PSm) under 200 μm; four, having a PSm under 180 μm, can be considered as fine or very fine and should be preferred by consumers. The grains of twenty-one maize cultivars of Benin including local ecotypes (5) and new cultivars (16) were physicochemically characterized and were tested for their ability to give fine whole grain flours. The five local ecotypes presented common traits such as high friability, low vitreousness, and dent kernel percentage giving relatively fine flours with low damaged starch content. On the contrary, most new cultivars had vitreous and hard grains and half gave very coarse flours with PSm over 200 μm. The more friable the grain was, the finer the whole grain flour it gave and the lower damaged starch it contained
Keywords: Maize; grain; hardness; physicochemical characteristics; milling; flour